Lineage‐specific adaptation to climate involves flowering time in North American Arabidopsis lyrata - Walden, Nora; Lucek, Kay; Willi, Yvonne (Molecular ecology, 2020)
see also the Perspective by Robin Burns and Polina Yu. Novikova